Pepper Novel Pseudo Response Regulator Protein CaPRR2 Modulates Drought and High Salt Tolerance - Lim, Junsub; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2021)
Plants modify their internal states to adapt to environmental stresses. Under environmental stress conditions, plants restrict their growth and development and activate defense responses. ABA is a major phytohormone that plays a crucial role in the osmotic stress response. In osmotic stress adaptation, plants regulate stomatal closure, osmoprotectant production, and gene expression. Here, we isolated CaPRR2—encoding a pseudo response regulator protein—from the leaves of pepper plants (Capsicum annuum). After exposure to ABA and environmental stresses such as drought and salt stresses, CaPRR2 expression in pepper leaves was significantly altered. Under drought and salt stress conditions, CaPRR2-silenced pepper plants exhibited enhanced osmotic stress tolerance, characterized by an enhanced ABA-induced stomatal closing and high MDA and proline contents, compared to the control pepper plants. Taken together, our data indicate that CaPRR2 negatively regulates osmotic stress tolerance.